Molecular Characterization and Elucidation of Pathways to Identify Novel Therapeutic Targets in Pulmonary Arterial Hypertension - Yao, Xiaoting; Jing, Tian; Wang, Tianxing; Gu, Chenxin; Chen, Xi; Chen, Fengqiang; Feng, Hao; Zhao, Huiying; Chen, Dekun; Ma, Wentao (Frontiers in Physiology, 2021)
Background: Pulmonary arterial hypertension (PAH) is a life-threatening chronic cardiopulmonary disease. However, there are limited studies reflecting the available biomarkers from separate gene expression profiles in PAH. The present study explored two microarray datasets by an integrative analysis to estimate the molecular signatures in PAH. Methods: Two microarray datasets (GSE53408 and GSE113439) were exploited to compare lung tissue transcriptomes of PAH patients and controls, and estimate differential expressed genes (DEGs). According to common DEGs of datasets, gene and protein overrepresentation analyses, protein-protein interactions (PPI), DEG-transcription factor (TF) interactions, DEG-microRNA (miRNA) interactions, drug-target protein interactions, and protein subcellular localizations were conducted in this study. Results: We obtained 38 common DEGs for these two datasets. Integration of the genome transcriptome datasets with biomolecular interactions revealed hub genes (HSP90AA1, ANGPT2, HSPD1, HSPH1, TTN, SPP1, SMC4, EEA1, and DKC1), transcription factors (FOXC1, FOXL1, GATA2, YY1, and SRF) and miRNAs (hsa-mir-17-5p, hsa-mir-26b-5p, hsa-mir-122–5p, hsa-mir-20a-5p, and hsa-mir-106b-5p). Protein-drug interactions indicated two compounds, including Nedocromil and SNX-5422, affecting the identification of PAH candidate biomolecules. Moreover, the molecular signatures were mostly localized in the extracellular and nuclear areas. Conclusions: In conclusion, several lung tissue-derived molecular signatures, highlighted in the present study, might serve as novel evidence for elucidating the essential mechanisms of PAH. The potential drugs associated with these molecules could thus contribute to the development of diagnostic and therapeutic strategies to ameliorate PAH.